Analysis of the demographic potential in function of tourism - Mijalce Gjorgievski (UTMS Journal of Economics, 2011)
Man is the prime mover of the overall social economic and political life of the entire globe and therefore he is studied from various aspects depending on the needs of what we want to obtain information on the demographic potential and its features. In this paper, the subject of study will be processing potential through its demographic characteristics (number condition, age structure, natural increase, economic activity, religious composition, etc.) for the tourism economy. We know that the basic elements of tourism are the natural and cultural wealth that detect, evaluate and put into operation in tourism. However, it has its function, the basic factor are the people who need to visit those places, so it is very important to understand the demographic characteristics of people in every region of the globe in order to come to some understanding of the habits, needs and affinities of people depending on age, nationality and religious affiliation, etc. when choosing their travel destination.
Keywords: 330; demographics; tourist; age structure; number of movements